Virtual theology, faith and adult education an interruptive pedagogy - Stuart-Buttle, Ros. (Newcastle upon Tyne : Cambridge Scholars Publishing, 2013)
Online learning is a key feature of the contemporary educational landscape and has entered mainstream policy, provision and practice. But if online education is to reach mature development and evaluation, it must be open to critical appraisal. This book considers the implementation of online learning within adult theological education. This can be an area of challenge or contention, especially when established academic practices and cherished values are seen as threatened when handed over to ...
Description based on print version record.
Keywords: Theology -- Study and teaching (Continuing education); Education -- Data processing; Religion; Religious education; Theology; RELIGION / Christian Education / General; Electronic books